Pengembangan Sistem Online Pendaftaran Santri Baru untuk Penguatan Manajemen Informasi Pondok Pesantren Islamiyah Syafi’iyah Situbondo - Fathorazi Nur Fajri; Wali Ja’far Shudiq; Nurul Hidayattun Nasyihin (Universitas Nurul Jadid, 2020)
New Santri Admission (Penerimaan Santri Baru) is an administrative process for the selection of new student candidates. The PSB process is always carried out manually at each school institution, especially the Islamic Boarding Schools, which will cause various difficulties from several related parties. Therefore the New Santri Admission System was created online or the term can be called the online PSB. . An idea emerged to create a new student admission information system based on the SQL database. With this system, pesantren or administrators can manage the implementation of student registration for web technology using the PHP programming language and new languages. such as rapid registration and announcements.